2012
DOI: 10.1021/bi300097g
|View full text |Cite
|
Sign up to set email alerts
|

Role of Coupled Dynamics in the Catalytic Activity of Prokaryotic-like Prolyl-tRNA Synthetases

Abstract: Prolyl-tRNA synthetases (ProRSs) have been shown to activate both cognate and some noncognate amino acids and attach them to specific tRNAPro substrates. For example, alanine, which is smaller than cognate proline, is misactivated by Escherichia coli ProRS. Mischarged Ala-tRNAPro is hydrolyzed by an editing domain (INS) that is distinct from the activation domain. It was previously shown that deletion of the INS greatly reduced cognate proline activation efficiency. In the present study, experimental and compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(72 citation statements)
references
References 52 publications
1
71
0
Order By: Relevance
“…The lack of activity of the path III variant suggests strong coupling between N305A and G412A since the effect of the double mutant (ΔΔ G > 3.7 based on level of detection of this assay) is greater than expected based on the single mutant effects (2.4 kcal/mol and 0.29 kcal/mol, for N305A and G412A, respectively). In a recent study, we showed that proline activation efficiency was reduced by ~ 50-fold in the E218A variant (16). Thus, the lack of activity of the path IV double mutants is not surprising.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The lack of activity of the path III variant suggests strong coupling between N305A and G412A since the effect of the double mutant (ΔΔ G > 3.7 based on level of detection of this assay) is greater than expected based on the single mutant effects (2.4 kcal/mol and 0.29 kcal/mol, for N305A and G412A, respectively). In a recent study, we showed that proline activation efficiency was reduced by ~ 50-fold in the E218A variant (16). Thus, the lack of activity of the path IV double mutants is not surprising.…”
Section: Resultsmentioning
confidence: 97%
“…Finally, the role of these selected residues in site-to-site communication was probed experimentally by conducting site-directed mutagenesis and kinetic studies. In addition, in silico mutations were performed and their impact on protein dynamics was examined by comparing root-mean-square (RMS) fluctuations of the WT and mutated variants (16). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the procedure have been described earlier [4, 7, 41]. The last 25 ns of the 30 ns MD simulation data was used to extract the principal modes of collective dynamics (called principal components) using the program CARMA [42].…”
Section: Methodsmentioning
confidence: 99%